Mononuclear Aluminum–Fluoride Ions, AlFx(+/−)—Study of Plausible Frameworks of Complexes with Biomolecules and Their In Vitro Toxicity - Anja Pavlovič; Larisa Janžič; Lucija Sršen; Andreja Nataša Kopitar; Kathleen F. Edwards; Joel F. Liebman; Maja Ponikvar-Svet (Molecules)
The importance of fluorine and aluminum in all aspects of daily life has led to an enormous increase in human exposure to these elements in their various forms. It is therefore important to understand the routes of exposure and to investigate and understand the potential toxicity. Of particular concern are aluminum–fluoride complexes (AlFx), which are able to mimic the natural isostructural phosphate group and influence the activity of numerous essential phosphoryl transferases. Our review of salts of ionic AlFx species, which plausibly form the framework of complexes with biomolecules, revealed that the octahedral configuration of aluminum in the active site of the enzyme is preferred over the trigonal-bipyramidal structure. The effects of varying concentrations of fluoride, aluminum and AlFx—from micromolar to millimolar levels—on the viability and apoptosis rate of THP-1 monocytes were investigated using phosphate buffer solution as a culture media to simulate physiological conditions. Our results suggest that aluminum can reduce the direct toxicity of fluoride through the formation of AlFx. In view of the results found, further in vitro studies are required to clarify the toxicity mechanisms of these species.